Behind the Zone of Avoidance of the Milky Way: What Can We Restore by Direct and Indirect Methods? - Vavilova, I.B.; Elyiv, A.A.; Vasylenko, M.Yu. (Радиофизика и радиоастрономия, 2018)
Purpose: to present a brief overview of methods for restoring the large-scale structure of the Universe behind the Zone of Avoidance (ZoA) of the Milky Way; to propose a new “algorithm of darning the ZoA” and new approach based on the Generative adversarial network (GAN) to recover galaxy distribution in the ZoA using optical surveys as an additional platform for programming the artificial neural networks.